Assessing Almond and Peanut Allergens Using Commercially Available Immunoanalytical Kits and LC-MS/MS: A Case Study. (23rd November 2019) - Daly, Matthew; Ansari, Parisa; Häubl, Georg; Rogers, Adrian; Brunner, Kurt
Abstract: With an ever-increasing allergic population and an emerging market for allergen-free foods, accurate detection of allergens in foods has never been more important. Although ELISA-based methods are the most widely used for detection of allergens in food, there is a need for the development of orthogonal approaches. A commercial ELISA detected a relatively high concentration of peanut and almond in an allergen-free product. However, another commercial ELISA declared a low peanut concentration and was negative for almond. Further testing using a commercial almond lateral-flow device confirmed the results from the second ELISA kit and demonstrated that the positive detection of almond was due to cross-reactivity. An MS method was used for final confirmation that the reported results were negative for both almond and peanut.